Answer:
![y=8 \cdot (\frac{5}{4})^x](https://tex.z-dn.net/?f=y%3D8%20%5Ccdot%20%28%5Cfrac%7B5%7D%7B4%7D%29%5Ex)
![f(x)=8 \cdot (\frac{5}{4})^x](https://tex.z-dn.net/?f=f%28x%29%3D8%20%5Ccdot%20%28%5Cfrac%7B5%7D%7B4%7D%29%5Ex)
or
![f(x)=8 \cdot (1.25)^x](https://tex.z-dn.net/?f=f%28x%29%3D8%20%5Ccdot%20%281.25%29%5Ex)
Step-by-step explanation:
We are going to see if the exponential curve is of the form:
, (
).
If you are given the
intercept, then
is easy to find.
It is just the
coordinate of the
intercept is your value for
.
(Why? The
intercept happens when
. Replacing
with 0 gives
. This says when
.)
So
.
So our function so far looks like this:
![y=8 \cdot b^x](https://tex.z-dn.net/?f=y%3D8%20%5Ccdot%20b%5Ex)
Now to find
we need another point. We have two more points. So we will find
using one of them and verify for our resulting equation works for the other.
Let's do this.
We are given
is a point on our curve.
So when
,
.
![10=8 \cdot b^1](https://tex.z-dn.net/?f=10%3D8%20%5Ccdot%20b%5E1)
![10=8 \cdot b](https://tex.z-dn.net/?f=10%3D8%20%5Ccdot%20b)
Divide both sides by 8:
![\frac{10}{8}=b](https://tex.z-dn.net/?f=%5Cfrac%7B10%7D%7B8%7D%3Db)
Reduce the fraction:
![\frac{5}{4}=b](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B4%7D%3Db)
So the equation if it works out for the other point given is:
![y=8 \cdot (\frac{5}{4})^x](https://tex.z-dn.net/?f=y%3D8%20%5Ccdot%20%28%5Cfrac%7B5%7D%7B4%7D%29%5Ex)
Let's try it. So the last point given that we need to satisfy is
.
This says when
,
.
Let's replace
with 2 and see what we get for
:
![y=8 \cdot (\frac{5}{4})^2](https://tex.z-dn.net/?f=y%3D8%20%5Ccdot%20%28%5Cfrac%7B5%7D%7B4%7D%29%5E2)
![y=8 \cdot \frac{25}{16}](https://tex.z-dn.net/?f=y%3D8%20%5Ccdot%20%5Cfrac%7B25%7D%7B16%7D)
![y=\frac{8}{16} \cdot 25](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B8%7D%7B16%7D%20%5Ccdot%2025)
![y=\frac{1}{2} \cdot 25}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B1%7D%7B2%7D%20%5Ccdot%2025%7D)
![y=\frac{25}{2}](https://tex.z-dn.net/?f=y%3D%5Cfrac%7B25%7D%7B2%7D)
![y=12.5](https://tex.z-dn.net/?f=y%3D12.5)
So we are good. We have found an equation satisfying all 3 points given.
The equation is
.
To do this you want to divide 110 by 5 to get 22. Now you want to multiply 3 by 22. That means the caterer need 66 pounds of tomatoes.
Answer:
Step-by-step explanation:
(x^2+y^2)^2=(x^2)^2+2x^2y^2+(y^2)^2
Adding and substracting 2x^2y^2
We get
(x^2+y^2)^2=(x^2)^2+2x^2y^2+(y^2)^2 +2x^2y^2-2x^2y^2
And we know a^2-2ab+b^2=(a-b)^2
So we identify (x^2)^2 as a^2 ,(y^2)^2 as b^2 and -2x^2y^2 as - 2ab. So we can rewrite (x^2+y^2)^2=(x^2 - y^2)^2 + 2x^2y^2 + 2x^2y^2= (x^2 - y^2)^2+4x^2y^2= (x^2 - y^2)^2+2^2x^2y^2
Moreever we know (a·b·c)^2=a^2·b^2·c^2 than means 2^2x^2y^2=(2x·y)^2
And (x^2+y^2)^2=(x^2 - y^2)^2 + (2x·y)^2
First, since we must follow PEMDAS, we need to do the operation that is first, which is addition.
-3.9 + 6.01 ← Adding a negative means subtracting, then giving the sign of the bigger number.
So now we solved those and we got this answer: 2.11
Now, we need to subtract and re-write the expression.
2.11 - (-7.423) = 2.11 + 7.423= 9.533
Ok....so now we have our final answer, and we have the choices above.
The only answer that matches ours is the last one.
Final answer: 9.533
Hope I helped ^_^